Reduced Pallidal Output Causes Dystonia - Nambu, Atsushi; Chiken, Satomi; Shashidharan, Pullanipally; Nishibayashi, Hiroki; Ogura, Mitsuhiro; Kakishita, Koji; Tanaka, Satoshi; Tachibana, Yoshihisa; Kita, Hitoshi; Itakura, Toru (Frontiers in Systems Neuroscience, 2011)
Dystonia is a neurological disorder characterized by sustained or repetitive involuntary muscle contractions and abnormal postures. In the present article, we will introduce our recent electrophysiological studies in hyperkinetic transgenic mice generated as a model of DYT1 dystonia and in a human cervical dystonia patient, and discuss the pathophysiology of dystonia on the basis of these electrophysiological findings. Recording of neuronal activity in the awake state of DYT1 dystonia model mice revealed reduced spontaneous activity with bursts and pauses in both internal (GPi) and external (GPe) segments of the globus pallidus. Electrical stimulation of the primary motor cortex evoked responses composed of excitation and subsequent long-lasting inhibition, the latter of which was never observed in normal mice. In addition, somatotopic arrangements were disorganized in the GPi and GPe of dystonia model mice. In a human cervical dystonia patient, electrical stimulation of the primary motor cortex evoked similar long-lasting inhibition in the GPi and GPe. Thus, reduced GPi output may cause increased thalamic and cortical activity, resulting in the involuntary movements observed in dystonia.